The Influence of Negative Pressure and of the Harvesting Site on the Characteristics of Human Adipose Tissue-Derived Stromal Cells from Lipoaspirates - Martina Travnickova; Julia Pajorova; Jana Zarubova; Nikola Krocilova; Martin Molitor; Lucie Bacakova (Stem Cells International)
Background. Adipose tissue-derived stromal cells (ADSCs) have great potential for cell-based therapies, including tissue engineering. However, various factors can influence the characteristics of isolated ADSCs. Methods. We studied the influence of the harvesting site, i.e., inner thigh (n=3), outer thigh (n=7), and abdomen (n=9), and of negative pressure, i.e., low (-200 mmHg) and high (-700 mmHg), on the characteristics of isolated ADSCs. We counted initial yields of attached cells after isolation. In subsequent passage, we studied the number, viability, diameter, doubling time, mitochondrial activity, and CD surface markers of isolated ADSCs. Results. We revealed higher initial cell yields from the outer thigh region than from the abdomen region. Negative pressure did not influence the cell yields from the outer thigh region, whereas the yields from the abdomen region were higher under high negative pressure than under low negative pressure. In the subsequent passage, in general, no significant relationship was identified between the different negative pressure and ADSC characteristics. No significant difference was observed in the characteristics of thigh ADSCs and abdomen ADSCs. Only on day 1, the diameter was significantly bigger in outer thigh ADSCs than in abdomen ADSCs. Moreover, we noted a tendency of thigh ADSCs (i.e., inner thigh+outer thigh) to reach a higher cell number on day 7. Discussion. The harvesting site and negative pressure can potentially influence initial cell yields from lipoaspirates. However, for subsequent in vitro culturing and for use in tissue engineering, it seems that the harvesting site and the level of negative pressure do not have a crucial or limiting effect on basic ADSC characteristics.